IMPLEMENTATION LEVEL OF INTEGRATED REPORTING AT MALAYSIA LOCAL AUTHORITIES - Sharifah Robiah Tuan Hazam; Noorhayati Mansor (International Journal of Accounting, Finance and Business, 2020)
In the private sector, integrated reporting is an emerging corporate reporting practice. Recently, the new reporting initiative starts to gain the attention of the public sector as well. Integrated reporting was designed to provide innovative and comprehensive reporting of performance with the main focus on value creations. The reporting classifies capitals into six types which are financial, manufactured, intellectual, human, social and relationship, and natural capital. The purpose of this study is to assess the implementation level of integrated reporting in the Malaysia local authorities which represent the third level of government administration. To date, no published empirical research has examined the issue at the level of local authority. The integrated reporting implementation is divided into high, moderate and low levels. This research adopts a quantitative approach and data was gathered using self-administrative questionnaire survey. 84 local authorities from 11 states in Peninsular Malaysia were involved in the study and 257 respondents made-up the final sample. The findings indicated that the overall implementation level was moderate at 56.4%. The results further revealed that only two states (Negeri Sembilan and Pahang) used the six capitals in the reporting while six other states (Selangor, Perak, Melaka, Johor, Kedah and Pulau Pinang) only reported four different capitals. The implementation level in the states of Kelantan and Perlis were still low at only 2 types of capital being reported. In terms of size, the findings suggest that the implementation levels at large and medium size local authorities were moderate at 66.7% and 70.9%, respectively. While the lowest level of implementation was recorded for the small size authorities with the mean of 53.2%. This study contributes to the current initiatives in promoting sustainable development goals at the local authorities in the Peninsular Malaysia through comprehensive reporting.